Formation of CH3NH2-incorporated intermediate state in CH3NH3PbI3 hybrid perovskite thin film formed by sequential vacuum evaporation. (26th November 2018) - Jung, Min-Cherl; Kobori, Sora; Matsuyama, Asuka; Maeng, Inhee; Lee, Young Mi; Kojima, Hirotaka; Benten, Hiroaki; Nakamura, Masakazu
Abstract: CH3 NH3 PbI3 thin films were formed with various deposition rates of PbI2 first layer using a sequential vacuum evaporation method (SVE) to understand the formation behavior. Under low PbI2 deposition rates with 1 and 3  Å s −1, the thin films did not form the hybrid perovskite structure. Over the 6  Å s −1 deposition rate, the perovskite structure is observed with the remaining PbI2 and an intermediate phase together. In the 10  Å s −1, the intermediate phase is increased, and the CH3 NH2 molecular defect is observed. The hybrid perovskite thin film formed by SVE is confirmed with tiny grains and CH3 NH2 -incorporated intermediate state.